2020
DOI: 10.3390/min10070619
|View full text |Cite
|
Sign up to set email alerts
|

An Improvement on Selective Separation by Applying Ultrasound to Rougher and Re-Cleaner Stages of Copper Flotation

Abstract: It has been known that the power ultrasound is used as a pretreatment and rarely applied as a simultaneous method to improve grade and recovery during froth flotation processes. This work aimed at investigating the impact of simultaneously used ultrasonic waves under variant operating configurations on the flotation of representative porphyry copper ore during rougher and re-cleaner stages. For this purpose, four different operating outlines were examined as (I) conventional flotation, (II) homogenizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 77 publications
0
9
0
2
Order By: Relevance
“…The beneficiation process can be also evaluated by means of the methodology presented in our previous works [79][80][81][82][83]. We recently presented the impact of configuration of sonication in four states on batch flotation of copper porphyry ore [31].…”
Section: Effect Of Sonication Power On Floatability Of Mono-mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficiation process can be also evaluated by means of the methodology presented in our previous works [79][80][81][82][83]. We recently presented the impact of configuration of sonication in four states on batch flotation of copper porphyry ore [31].…”
Section: Effect Of Sonication Power On Floatability Of Mono-mineralsmentioning
confidence: 99%
“…Despite there are several investigations indicated the application of ultrasonic waves during the coal flotation processes [17,18,[23][24][25], there is a considerable lack of study on simultaneous ultrasonic vibration in the mineral flotation processes. To the best of the author's knowledge, it is only limited to colemanite [26], graphite [27], galena [28,29], phosphate [30], magnesite [11], ilmenite [12], copper ore [31][32][33][34], copper tailing [35], chalcopyrite [36], scheelite ore [37,38], barite-fluorite-quartz ore [39], lead-zinc-copper ore [40], quartz [13,22] and silica [41,42], calcite and barite [43], talc [44] and feldspar [14] in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Öte [14,20,21,45]. Ayrıca, ultrasonik kavitasyonun su ve yağ arasındaki arayüzey gerilimini azaltarak yağ damlacıklarını küçük ve kararlı hale getirdiği ve aglomerasyon sürecini iyileştirdiği düşünülmüştür [37,43,44]. Öte yandan, ultrasonik sistemin kullanılmadığı deneylerde, atık yağ oranına bağlı olarak yanabilir kömür verim değerleri artarken, ultrasonik sistemin kullanıldığı deneylerde, özellikle yüksek güç değerlerinde yanabilir verim değerleri azalmaktadır.…”
Section: Materyal Ve Yöntemunclassified
“…However, Dixon et al (2008) reported that the pyrite to chalcopyrite ratio must be in the range of two to four to achieve a reasonable recovery, and Koleini et al (2010) indicated a mass ratio of over 4. It was reported that pyrite forms hydrogen peroxide (H2O2) by being drawn in water, which is a strong oxidant agent (Nooshabadi et al, 2013;Hassanzadeh et al, 2020). Interestingly, this principle fact and its effectiveness on chalcopyrite electro-leaching have been relatively overlooked in the literature, which needs to be studied in future works.…”
Section: Introductionmentioning
confidence: 99%